Immersive virtual reality for extending the potential of building information modeling in architecture, engineering, and construction sector: systematic review. Issue 1 (31st December 2022) - Safikhani, Saeed; Keller, Stephan; Schweiger, Gerald; Pirker, Johanna
ABSTRACT: The field of architecture, engineering, and construction (AEC) is continually striving to use resources efficiently and manage complex processes. Now more than ever, there is a strong need for digital transformation in AEC. The improvement in the accessibility of consumer-based head-mounted displays (HMD) is attracting different entertainment and research fields to immersive virtual reality (VR) applications. Building Information Modeling (BIM) is known as a promising technology in AEC. The full potential of BIM is not yet employed to empower this field, however, and this could be a result of some barriers still to be surmounted by BIM in both technological and management perspectives. One of these barriers is the communication and collaboration between design, construction, operation, and maintenance phases. VR can fill this gap by providing additional capabilities for BIM which either were not available before or were not possible to employ in practical ways. In this paper, we systematically review recent research around the application of VR in BIM and discuss the results using the PRISMA flowchart. We discuss the most commonly used technologies, software, and evaluation methods and the various applications of VR in the reviewed papers. Finally, we extend the discussion by summarizing the potential future work in this area.